Vendor Managed Inventory:Retail Industry Perspective of Malaysia - Madjlesi Taklimi, Zahra (2011)
The concept of Vendor Managed Inventory (VMI) radically changes a traditional inventory management. Under the typical business model, the buyer or retailer is in total control of the timing and volume of the order, in order placing and managing the inventory plan. Whereas VMI is a supply chain initiative where the supplier is responsible for all decisions regarding inventories at the retailers, i.e. under VMI program the supplier is authorized to manage inventories of agreed-upon stock-keeping units at retail locations. This technique is one of the most widely discussed partnering initiatives for improving multi-firm supply chain efficiency which was popularized in the late 1980’s by Wal-Mart and Procter & Gamble. The benefits of VMI are well recognized by successful retail businesses. For instance, bullwhip effect is minimized, stock-out situations are less frequent, and inventory-carrying costs are reduced. Although there are a number of studies about VMI in different business environment of different countries, there is not any published research in this respect in Malaysia’s retail industry. Retailing not only has been one of the most active sectors in the Malaysian economy, but also has contributed significantly to Malaysia GDP. So, improving the retail industry through advanced programs such as VMI can improve the economy of Malaysia. This study aims to address VMI implementation in Malaysia’s retail industry by following grounded theory as one of the dominate influences on qualitative method. In particular, this study is going to achieve three research objectives including 1- To identify VMI’s benefits comparison by typical inventory management, 2- To examine whether VMI is an effectual system to solve retail industry’s current problems, i.e. to improve its current situation, and 3- To identify the barriers and drivers for implementing VMI in Malaysia’s retail industry to come to this conclusion whether VMI is implementable in Malaysia’s retail industry. The first research objective is fulfilled through reviewing relevant literature, and two last objectives are achieved by examining the empirical data which have been collected through semi-structured interviews with different players of Malaysia’s retail industry. This empirical study, through answering the mentioned research questions, concludes VMI as a SCM initiative is able to solve or to mitigate the most common problems of Malaysia’s retail industry. Yet, considering existing barriers for implementing VMI in Malaysia’s retail industry, this technique is not practicable in this sector especially in present situation. Finally, the author recommends future research more focused on implementing co-managed inventory as a form of VMI which involves a more actively collaborative approach between supply-chain partners by sharing the responsibility for inventory management.